2021
DOI: 10.1532/hsf.3409
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana: An Underappreciated Risk Factor for Acute Type A Aortic Dissection?

Abstract: Background: Stimulants such as cocaine and amphetamines are well-established risk factors for acute aortic dissection. Despite the fact that marijuana is the most commonly used illicit drug in the United States, its relationship to acute aortic syndromes has not been well studied. Methods: A comprehensive retrospective review was undertaken of all consecutive patients who presented with acute Stanford type A aortic dissection from January 2017 to December 2019. Of 152 patients identified, 51 (33.6%) underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…Of the 20 included studies, a total of 183,410,651 patients were enrolled with the number of participants in each study ranging from 51 to 118,659,619 patients. [10] , [11] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] The median age was 42.4 years old (IQR: 37.4, 50.0). The proportion of males was 23.7%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 20 included studies, a total of 183,410,651 patients were enrolled with the number of participants in each study ranging from 51 to 118,659,619 patients. [10] , [11] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] The median age was 42.4 years old (IQR: 37.4, 50.0). The proportion of males was 23.7%.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies with a total of 172,285,631 patients reported stroke, which occurred in 248,563 patients (0.14%) [10] , [24] , [25] , [27] , [28] , [29] , [33] , [34] , [35] , [36] , [37] , [38] , [40] . The pooled OR and rates of stroke were shown in [ Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Marijuana taken with other stimulants can increase the heart rate, blood pressure, and systemic sympathetic tone [119] . Nevertheless, Sarmiento et al did not observe short-term mortality differences in groups with or without marijuana abuse [120] . Re-intervention, long-term poor physical condition, and a high rate of complications may affect marijuana users.…”
Section: Drug Abuse and Covid-19mentioning
confidence: 99%